Genome-wide identification and expression analysis of rice NLR genes responsive to the infections of Xanthomonas oryzae pv. oryzae and Magnaporthe oryzae. (August 2020) - Ding, Li; Xu, Xiameng; Kong, Weiwen; Xia, Xue; Zhang, Shengwei; Liu, Li-Wei; Liu, Aixin; Zou, Lifang
Abstract: Nucleotide-binding site, leucine-rich repeat ( NLR ) genes play a critical role in rice disease resistance. However, the transcriptional activities of rice NLR genes during pathogen invasions are still unclear. To uncover their activities, we identified 430 regular rice NLR genes with both NBS and LRR domains, consisting of 192 CNL and 238 XNL (without a CC motif) members. We performed individual and integrative analyses based on 69 samples from rice microarray after the infections of Xanthomonas oryzae pv. oryzae ( Xoo ) and Magnaporthe oryzae ( Mor ). Among the rice NLR genes, 397 were found to be expressed at low/medium level, while 10 NLR genes were observed to show high expression levels. A total of 400 NLR genes were discovered to be differentially expressed in at least one sample. Furthermore, 46 rice NLR genes were identified to be differentially expressed in response to the two pathogens and 38 of them could be validated using RNA-seq data. Six cis -regulatory elements (MYC, STRE, MYB, ABRE, G-box, and AS-1) were observed to occur frequently in the promoter regions of rice NLR genes. Ten NLR genes were selected for qPCR detection, and seven of the NLR genes verified the validity of the microarray and RNA-seq data. Our results are helpful in revealing expressions and regulations of NLR genes in rice resistance to Xoo and Mor . Highlights: 430 regular rice NLR genes were identified. 10 rice NLR genes showed high levels of expression. 400 rice NLR genes were differentially expressed in at least one sample. 46 rice NLR genes were differentially expressed in response to both Xoo and Mor. Six cis -regulatory elements are occurring frequently in rice NLR promoter regions.